PERSONAL POLITICAL BRANDING FOR ELECTABILITY BOOST: THE EVIDENCE FROM MILLENNIAL LOCAL LEADERS IN WEST SUMATERA - Athahirah, Astika Ummy (Universitas Padjadjaran, 2024)
Today, creating a personal political brand is essential for regional heads to increase electability ahead of regional elections. This research explores how elected millennial regional heads create, develop, and communicate their political brands to increase their electability in West Sumatera, Indonesia. The authors used an exploratory approach and data collection through primary data obtained from semi-structured interviews and surveys using questionnaires. Secondary data includes journals, online newspapers, the official website of the General Elections Commission (KPU), the Central Statistics Agency (BPS), and social media. This research also used a quasi-qualitative design that goes through several stages, starting with exploring the research problem to confirm a new theory. Here, we show that they created personal political brands through the legacy and experiences of families and regional leaders. They also take several stages in building a personal political brand, namely conducting introspective investigations and evaluations through brand mantras offline and online traces. Later, their involvement in several organizations also became a determinant of political branding. The final stage in building this personal political brand is to evaluate the existing brand. Therefore, this research can be a reference for candidates for regional heads and legislators who are building their political brands. Given the limitations of this study, the authors suggest conducting follow-up research from another point of view of the political brand and its political marketing strategy.